PD-1 Blockade on Tumor Microenvironment-Resident ILC2s Promotes TNF-α Production and Restricts Progression of Metastatic Melanoma - Howard, Emily; Hurrell, Benjamin P.; Helou, Doumet Georges; Quach, Christine; Painter, Jacob D.; Shafiei-Jahani, Pedram; Fung, Marshall; Gill, Parkash S.; Soroosh, Pejman; Sharpe, Arlene H.; Akbari, Omid (Frontiers in Immunology, 2021)
While pulmonary ILC2s represent the most dominant tissue-resident innate lymphoid cell population at steady state and are key drivers of cytokine secretion in their occupational niche, their role in pulmonary cancer progression remains unclear. As the programmed cell death protein-1 (PD-1) plays a major role in cancer immunotherapy and immunoregulatory properties, here we investigate the specific effect of PD-1 inhibition on ILC2s during pulmonary B16 melanoma cancer metastasis. We demonstrate that PD-1 inhibition on ILC2s suppresses B16 tumor growth. Further, PD-1 inhibition upregulates pulmonary ILC2-derived TNF-α production, a cytotoxic cytokine that directly induces cell death in B16 cells, independent of adaptive immunity. Together, these results highlight the importance of ILC2s and their anti-tumor role in pulmonary B16 cancer progression during PD-1 inhibitory immunotherapy.